Epidemiological Characteristics of Clubfoot Patients in Selected Hospitals of Dhaka City (Ibrahim Cardiac Medical Journal, 2016)
Background and Objectives: Congenital clubfoot or talipes equinovarus is the most common birth defect of the musculoskeletal system affecting 1 in every 1000 live births each year. To date, no epidemiological studies have been conducted in Bangladesh to assess the risk factors associated with this deformity. The purpose of this study was to evaluate the specific demographic and socioeconomic factors that may increase the risk of an infant being born with clubfoot as well as to see the outcome of management of clubfoot.Materials and methods: The present prospective study was conducted on secondary data derived from the Project "Walk for Life (WFL)" started in Bangladesh in 2009 and gradually expanded to 35 Clinics. The present study data were collected from 5 of those clinics namely NITOR, DMCH, BSMMU, ICMH and CRP. All recruited cases underwent Ponseti casting. Demographic data, Pirani scores, cast and need for tenotomy were reviewed for 338 patients registered in the above 5 clinics during the period 2012. The outcome was evaluated with help of difference between the Pirani scores before and after intervention.Result: In the present study about half (48.5%) of the children presented at 1 or < 1 month of age with median age of the children being 2 months and a wider age-range from 1 month to 42 months. A male preponderance (72%) was observed in the series. Children with clubfoot were predominantly belonged to poor family (mostly labour or unemployed, lives in tin-shaded house, with monthly income below Taka 10000). About half (48.2%) of the parents/guardians were informed about the place of clubfoot treatment (NITOR, DMCH, BSMMU, ICMH and CRP) from their primary physicians, 23.7% from the parents of the children who previously got treatment from the centers and only 16% from publicity. In terms of treatment provided, more than three-quarters were given 4 - 6 casts and in 80% cases tenotomy was needed. Majority of the children (9.5%) before intervention exhibited a Pirani score from 3.1 - 6.0 which after a mean period 5 weeks of intervention was reduced to 0.5 - 1.0 (the targeted Pirani score) in almost all cases. Only 2 children were referred. The rest 336 were continuing their treatment and as such the final comment was left pending.Conclusion: Children presented with clubfoot in tertiary level hospitals of Bangladesh are mostly male, belonged to poor family. Half of the children are bilaterally affected and attend in the treatment centers within one month of birth. The primary physicians are the prime source of information about the treatment centers. Mass media are less involved in giving the issue a wide coverage. Majority of the children responded well to 4 - 6 casts and required tenotomy.Ibrahim Cardiac Med J 2014; 4(2): 16-20